2017
DOI: 10.12973/ejmste/80802
|View full text |Cite
|
Sign up to set email alerts
|

Study of Educators’ and Parents’ Readiness to Implement Distance Learning Technologies in Preschool Education in Russia

Abstract: The urgency of this research is determined by the need to study the readiness of school community in preschool educational establishments of Russia to apply distance learning technologies. The purpose of the research is to study motivation and valuebased, cognitive, operational (operational-activity), emotional-volitional, and information components of the readiness of preschool teachers and parents of preschool children to implement distance learning technologies in a major city and in rural areas. A sociolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…"Life informatization" imposes new demands on using ICT (information and communication technologies) at each level of the educational system (Baş, Kubiatko & Sünbül, 2016;Fedina, Burmykina, Zvezda, Pikalova, Skudnev & Voronin 2017). Technical and technological development has induced changes in every sphere of society, including education (Doulík, Škoda & Šimonová, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…"Life informatization" imposes new demands on using ICT (information and communication technologies) at each level of the educational system (Baş, Kubiatko & Sünbül, 2016;Fedina, Burmykina, Zvezda, Pikalova, Skudnev & Voronin 2017). Technical and technological development has induced changes in every sphere of society, including education (Doulík, Škoda & Šimonová, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From another perspective, Ventayen and Orlanda (2018) showed that there was a positive attitude among graduate students towards open distance elearning. In a similar study, Fedina et al, (2017) concluded in their study that preschool educational institution (PEI) administration considers their educational institution ready for distance learning technology (DET). However, from the paper of Alea et al, (2020), they explained that the teachers' geographical location correlates to the readiness to adapt to distance learning education.…”
Section: Resultsmentioning
confidence: 99%
“…The second part is a 5-point Likert-based 15-item questionnaire which captured respondents' perceived school readiness in each of the three identified distance learning modalities; modular distance learning (1-5), online distance learning (6-10), and TV-Radio based distance learning (11)(12)(13)(14)(15). Most of the descriptions are taken from DepEd Central Office Memorandum DM-CI-2020-00162, which suggests actions and strategies employed by most public schools in the country.…”
Section: Research Instrumentmentioning
confidence: 99%